Christian faith and social transformation : John Howard Yoder's social ethics as lens for revisioning the ecclesiological identity of the South Central Synod (SCS) of the Presbyterian Church of Nigeria (The PCN) - Ndukwe, Olo (Stellenbosch : Stellenbosch University, 2008)
Thesis (DTh (Systematic Theology and Ecclesiology))—Stellenbosch University, 2008.